Définition d’un espace de pratique du système littoral touristique et sportif charentais : le spot de surf - Valentin Guyonnard; Luc Vacher (Territoire en Mouvement, 2016)
The definition of a coastal territory as a tourist destination but also as a tourism and leisure practice area is at the centre of the thinking on the coastal systems organisation. To understand how these practice areas relate to each other, it is however necessary to define them. In this paper, we explain how the surf spot, which is an emblematic coastal practice area that can participate in defining a strong tourist communication, is defined through use of space. This work is based on data produced at Pertuis sea scale (Charente-Maritime coast) by Observatoire des pratiques de tourisme et de loisir of the research unit UMR LIENSs(LIttoral ENvironnement et Sociétés) CNRS-Université de La Rochelle. To understand how to define these spaces, this presentation will be organized in three parts. First, the analysis of the reputation of surf spots in the communication of different actors involved in surfing system will define a list of high places and permit to see how these places are spatially defined. This mapping will then be confronted with beach attendance data collected by the Observatoire des pratiques. This examination of the data show that the limits between surf spots are sometimes blurred and the operation of these places incorporates a sliding scale in time and in space. This analysis will be validated in a last stage by the study of surfing session GPS traces showing amplitude and shape of the spatial impact of the practice.